RI 3194 Inflammable Gases Produced By Thermal Decomposition of Plastic Insulators in an Electric Arc - J. B. Littlefield; W. P. Yana (The National Institute for Occupational Safety and Health (NIOSH), 1932)
"INTRODUCTION AND OBJECT OF EXPERIMENTAn explosion in and rupture of a gas-tight switch box on an electric loader in a mine located near Pittsburgh indicated that the cause was an internally generated inflammable gas-air mixture. This led to the suspicion that moisture condensation or ""other unusual conditions might have caused a spark or are across the surface of the material and that the heat may have created a carbonized path across the synthetic plastic base which would then conduct a large current with the generation of considerable heat and thermal decomposition of the base materials base in the box which exploded gave every indication that this series of events had taken place, and accordingly it was desired to determine what explosive gases such a decomposition of these insulating materials would produce.ACKNOWNLEDGMENTSThe desirability of making this investigation was suggested to the authors by L. O. Ilsley, supervising engineer, electrical section, Bureau of Mines, to whom the occurrence of an explosion in a switch box had been reported. The writers also acknowledge with thanks the assistance of L. B. Berger, chief scientific aide, health laboratory section, Bureau of Mines, in checking the calculations in the tables. DESCRIPTION OF MATERIAL INVESTIGATEDThe ten materials used in the tests, identified by letters A to J inclusive, are described in a succeeding list of materials. All the materials except I had a phenolic odor, especially when freshly cut."